STUDI ALOKASI WAKTU PEREMPUAN PEKERJA TELUR IKAN TORANI DALAM RUMAH TANGGA DAN RANAH PUBLIK - Harianto, Dedi; Romadin, Achmad; Ahmad, Ahmad; Irfan, Andi Muhammad; Slamet, M. Aji (DISCOURSE: Indonesian Journal of Social Studies and Education, 2024)
Torani fish eggs have become an important part of Takalar District's livelihoods and household economics. Mothers make up the vast majority of the Torani fish egg management workforce. Women's dual function in modern society has evolved significantly. The purpose of this study is to look into how female Torani fish egg workers allocate their time. The study employs a qualitative methodology. The study discovered that married female Torani fish egg workers split their time between housework and work outside the home. Although they work 8-10 hours every day, they spend most of their free time with their family. Economic circumstances, kid population, and educational level all contribute to this dual role. However, their public appearance contributes to the family's requirements. Despite this, social connection within the family is intact, and parents continue to instill values in their offspring.